2017
DOI: 10.1002/rrq.175
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Together Reading and Writing: An Experimental Study of Writing Intensive Reading Comprehension in Low‐Performing Urban Elementary Schools

Abstract: A B S T R A C TThis study examined the hypothesis that assisted writing during reading improves reading comprehension. The hypothesis was derived from sociocognitive and constructivist theory and research and implemented in the form of a curricular intervention called Writing Intensive Reading Comprehension after its main feature of bringing together reading comprehension and writing. The study used instruction with interactive thinksheets to provide sustained, focused, and assisted writing experiences to help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Taken together, all three scores reflect students’ science domain knowledge and argument structure knowledge. Relatively high interrater agreement (Cohen’s κ = .74 for a total writing scores and Cohen’s κ = .90 for agreement within one score point) was at a level consistent with intervention studies involving ratings of student writing in the elementary grades (Coker et al, 2016; Collins, Lee, Fox, & Madigan, 2017).…”
Section: Methodssupporting
confidence: 69%
“…Taken together, all three scores reflect students’ science domain knowledge and argument structure knowledge. Relatively high interrater agreement (Cohen’s κ = .74 for a total writing scores and Cohen’s κ = .90 for agreement within one score point) was at a level consistent with intervention studies involving ratings of student writing in the elementary grades (Coker et al, 2016; Collins, Lee, Fox, & Madigan, 2017).…”
Section: Methodssupporting
confidence: 69%
“…Accomplishing equivalent comparison can be difficult. In a study of writing to improve reading comprehension (Collins, Lee, Fox, & Madigan, 2017), there were 1,062 students and 49 teachers/classrooms. The researchers wanted to randomly assign teachers to the two groups: business-as-usual reading comprehension instruction and the writing about texts innovation.…”
Section: Was There a Comparison Group And Were The Groups Equal At Tmentioning
confidence: 99%
“…Collins, Lee, Fox, and Madigan (2017) examined the effects of integrated reading and writing instruction on the reading comprehension of 1,062 fourth-and fifth-grade students in low-performing schools. Results indicated that integrated reading and writing facilitated by thinksheets (graphic organizers) improved reading comprehension better than traditional instruction.…”
Section: Analytic Text-based Essay Writingmentioning
confidence: 99%